Community English In Program Training For Active and Smart Vacational High School Students (CEPAT FASIH) Di SMK Mamba’ul Ihsan Ujungpangkah Gresik - Sulistiyani Sulistiyani (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2023)
The purpose of this service is to increase creativity so that students get used to listening to communication in English and can actively speak English, so this community service is aimed at partners, namely: MAMBAUL IHSAN VOCATIONAL SCHOOL, as many as ten teachers were involved. Based on the description of the existing situation analysis, the problems of the partners are: Several solutions are offered: Providing workshop training to vocational school teachers, especially English subject teachers regarding: a) Teaching English in a joyful learning and through a communicative approach . b) Administration and learning tools are equipped according to the learning curriculum. c) Making teaching aids in the form of images/ audio visual as learning media. d) Increase the number of media and understand various learning methods to foster teacher creativity. e) Build facilities and infrastructure. f) Conduct training for teachers in designing learning tools. In addition, the results achieved in the form of methods in settlement for partners are as follows: 1) Conduct Information and Technology (IT) training which is summarized in the workshop : Internet and its network 2) Workshop which also includes training